Apakah Peran Etika Kerja Islam Memoderasi Objektivitas dan Komitmen Profesi Terhadap Moral Disengagement Akuntan di Indonesia? - Mais, Rimi Gusliana; Hidayah, Nurul; Munir , Munir; Widyastuti Wulaningsih, Ririn (Universitas Muhammadiyah Malang, 2024)
Purpose: This study purpose is to provide empirical evidence of the role of Islamic work ethics in moderating objectivity and professional commitment to moral disengagement of Indonesian accountants. Methodology/approach: This research is descriptive quantitative, which is measured using the SEM PLS analysis method using the Smart PLS application. Respondents in this research are individuals who work as accountants, auditors and financial staff who work in the Jabodetabek area. Data collection by filling out questionnaires by 214 sample respondents. Hypothesis testing using the p-value test on the boostrapping menu in the SmartPLS application. Findings: The research results prove that (1) Objectivity has a negative effect on moral disengagement; (2) Professional commitment has a negative effect on moral disengagement; (3) Islamic work ethics have a negative effect on moral disengagement; (4) Objectivity with moral disengagement is not moderated by Islamic work ethics; (5) Professional commitment with moral disengagement is not moderated by Islamic work ethics. Practical implications: The implications of the research results provide evidence of the importance of implementing Islamic work ethics in the work environment of accounting offices and the public accounting profession. Originality/value: This research investigates the rarely explored area of accounting morality and includes Islamic work ethics as a key variable. By measuring accountants' moral disengagement, this study provides valuable insights into this field and presents a fresh perspective for future research. This research is one of the few studies that includes Islamic work ethics as a variable when measuring accountants' moral disengagement.